The political knowledge of Libyan university students: Sirte and Omar Al-Mukhtar universities as two examples. Issue 4 (2nd October 2017) - Alsati, Alfeetouri Salih
ABSTRACT: This article reports on a study measuring the political knowledge of a sample of students at the Sirte and Omar Al-Mukhtar universities in Libya in 2015–2016. Variables such as the university attendees, gender, residence, type of faculty, family's economic condition and parents' educational level were factored into the analysis, and a sample of 400 students from the two universities was selected to provide survey data. Findings indicate that acquiring political knowledge, as a whole, requires great effort to accommodate Libya's current circumstances. Variables of gender, residence and university type make a difference in the level of political knowledge. While income and the level of parents' education do not determine the extent of political knowledge, the value placed on citizenship was found to have a strong effect on the variation in legal and political knowledge and on the students' understanding of the political process.